Teoretyczne i praktyczne aspekty strategii bezpośredniego celu inflacyjnego - Mela, Ewelina (Theoretical and practical aspects of direct inflation target strategy, 2007)
In recent years there has been a growing trend toward the adoption of so-called direct inflation target strategy as the primary focus for the conduct of monetary policy. Direct inflation target is designed to help the central bank achieve long-run price stability. Within its framework the central bank defines the inflation target in a quantified fonu and then adjusts the level of official interest rates so as to maximize the probability of its being achieved. Important features of inflation targeting include increased communication with the public about the plans and objectives of the monetary policy and increased accountability of the central bank for attaining this objective. Inflation targeting in various forms has been adopted by many countries, including Canada, United Kingdom, Sweden, Australia, Finland, Spain and New Zealand. Monetary Policy Council of the National Bank of Poland has adopted direct inflation targeting in 1998. This paper besides some theoretical elements of inflation targeting presents details of how this approach has been implemented in practice.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1189, s. 113-123